Determinación de la concentración de mercurio en tierras de cultivo impactadas por la minería artesanal en el cerro El Toro, Shiracmaca -Huamachuco, La Libertad - 2012 - Ramos Peña, Sarita Teresa (2012)
The concentration of mercury in farmland impacted by artisanal mining in the Cerro El Toro, Shiracmaca-Huamachuco, La Libertad - 2012, including a description of the mercury concentration in cropland areas adjacent to the Cerro El Toro , for it was sampled at three points at three different times were analyzed by the method of atomic absorption spectrophotometry. In the determination of mercury in farmland in the three samples showed average: M1 (728,511 ppb), M2 (1013.489 ppb) and M3 (769,511 ppb), all samples showing concentrations above the permissible critical limits to prevent ecological effects from 0.07 to 0.3 mg / kg (70 - 300 mg / kg or ppb) of total mercury in soils, as indicated in the assessment by the United Nations Program for Environment (UNEP) - 2010